Keabsahan Fatwa Dewan Syariah Nasional Dalam Penyelenggaraan Asuransi Syariah Di Indonesia - Atin Meriati Isnaini (Fakultas Hukum Universitas Mataram, 2016)
Once the importance of the DSN to be used as guidelines for conducting business review Takaful, which contained hearts DSN-MUI Fatwa No.21 / DSN-MUI / X / 2001 Guidelines for General Takaful, the fatwa issued regulations Yang BECAUSE THERE IS can be used as guidelines to review the activities run Takaful. But the DSN-MUI fatwa are NOT have the legal force of the National Legal hearts hearts BECAUSE including legislation in Indonesia.Penelitian Singer-focused normative juridical validity showed to the National Sharia Board Fatwa Council of Ulama Indonesia, WITH approach using legislation and approach conceptual. Validity DSN - MUI can be the apparently hearts some ASPECT; First, DSN - MUI NOT known hearts of Law No. 12 of 2011; Second, DSN - MUI is a prayer One source of national law; Third, sociological Operates keberlakukan DSN - MUI accepted by All elements of the nation and gatra. But the validity of DSN - MUI still has drawbacks.